Building Capacity for Trauma-Informed Care in the Child Welfare System: Initial Results of a Statewide Implementation. (May 2016) - Lang, Jason M.; Campbell, Kimberly; Shanley, Paul; Crusto, Cindy A.; Connell, Christian M.
Exposure to childhood trauma is a major public health concern and is especially prevalent among children in the child welfare system (CWS). State and tribal CWSs are increasingly focusing efforts on identifying and serving children exposed to trauma through the creation of trauma-informed systems. This evaluation of a statewide initiative in Connecticut describes the strategies used to create a trauma-informed CWS, including workforce development, trauma screening, policy change, and improved access to evidence-based trauma-focused treatments during the initial 2-year implementation period. Changes in system readiness and capacity to deliver trauma-informed care were evaluated using stratified random samples of child welfare staff who completed a comprehensive assessment prior to ( N = 223) and 2 years following implementation ( N = 231). Results indicated significant improvements in trauma-informed knowledge, practice, and collaboration across nearly all child welfare domains assessed, suggesting system-wide improvements in readiness and capacity to provide trauma-informed care. Variability across domains was observed, and frontline staff reported greater improvements than supervisors/managers in some domains. Lessons learned and recommendations for implementation and evaluation of trauma-informed care in child welfare and other child-serving systems are discussed.